An overview of a 30-year experience with amniocentesis in a single tertiary medical center in Taiwan - Yi-Wen Chang; Chia-Ming Chang; Pi-Lin Sung; Ming-Jie Yang; Wai Hou Li; Hsin-Yang Li; Ling-Chao Chen; Ling-Yi Cheng; Yu-Ling Lai; Yung-Yung Cheng; Wen-Hsun Chang; Kuan-Chong Chao; et al. (Elsevier, 2012)
Objective: Amniocentesis is a popular and effective prenatal diagnostic tool for chromosomal disorders. It is well-established that the risk of chromosomal abnormalities increases with maternal age; however, other related indications are seldom reported. Herein, we report our 30-year experience with amniocentesis from a single medical center, focusing on the indications and rates of abnormality. Material and Methods: A retrospective review of 16,749 pregnant women in the mid-trimester between January 1981 and December 2010 was conducted. The medical records were analyzed. Results: The indications for amniocentesis were advanced maternal age (≥ 34 years old) (n=10,970, 65.5%), increasing-risk maternal triple-marker Down's screening test (≥ 1/270) (n=2090, 12.5%), history of abnormal offspring birth (n=792, 4.7%), abnormal ultrasound findings (n=484, 2.9%), parent with abnormal karyotype (n=252, 1.5%), family history of chromosomal abnormality (n=183, 1.1%), drug and radiation exposure (n=165), abnormal chorionic villus sampling (CVS) results (n=25), intrauterine fetal death (n=50), and other non-specific causes (n=1662, 9.9%). The rate of abnormality for each indication was 16% in the abnormal CVS group, 12% in the intrauterine fetal death group, 11.5% for parental chromosomal abnormality, 8.7% in the abnormal ultrasound finding group, 3.0% in the increasing-risk maternal triple-marker Down's screening test group, 2.5% in the advanced maternal age group, 1.5% for other non-specific causes, 1.4% for history of abnormal offspring birth, and 1.1% for family history of chromosomal abnormality. Conclusions: Both parents with abnormal karyotype and abnormal ultrasound findings are indications for which consideration of further amniocentesis is highly recommended.